Orientação sexual: responsabilidades da escola e da família - Flose, Keila Rocumback (2014)
This research work has owned focused on research of the existence of taboo to address the Sexual Orientation in the school and family environment, and to investigate the ways in which people deal with it. During the research were heard students, teachers, parents and guardians seeking to solve doubts about it. Through the use of specific questionnaires for each group, we tried to confront the opinions of each group, and two state schools in the Embu Guaçu region participated. At the end of the work, were built graphs showing the search results. Addressing this issue is strange, because there are several aspects that influence the subject, such as religious beliefs; family and social aspects; among others. The importance of this issue can not be forgotten, because, every year growing numbers of adolescents infected with sexually transmitted diseases such as HIV, for example. Early pregnancy rates are also alarming. The curious thing is that we live in the age of communication and technology, and our young people not yet seem to have enough information to prevent.